2022
DOI: 10.1111/cas.15368
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐21 promotes metastasis via increasing the recruitment and M2 polarization of macrophages in HCC

Abstract: MMP-21 is a newly identified member of the matrix metalloproteinase family and has been reported to regulate both embryonic development and tumor progression.However, the roles of MMP-21 in hemofiltrate C-C chemokine (HCC) remain largely unclear. In this study, we used western blot, qPCR and immunohistochemistry (IHC) to determine the upregulation of MMP-21 in HCC tissues, and showed that the increase in MMP-21 was associated with vascular invasion and poor prognosis. Although changing levels of MMP-21 in HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The correlation analysis between immune cells, expression of hub UbRGs, and risk scores revealed a strong positive correlation between macrophages and ubiquitination genes (Figure 7 F). M2 macrophages are recognized as crucial contributors to tumor progression and have been associated with poor prognoses 38 . Ubiquitin promotes macrophage M2 polarization and activates the CXCR4/ERK signaling pathway, thereby facilitating the invasion of HCC 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis between immune cells, expression of hub UbRGs, and risk scores revealed a strong positive correlation between macrophages and ubiquitination genes (Figure 7 F). M2 macrophages are recognized as crucial contributors to tumor progression and have been associated with poor prognoses 38 . Ubiquitin promotes macrophage M2 polarization and activates the CXCR4/ERK signaling pathway, thereby facilitating the invasion of HCC 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the overexpression of CCL14 inhibits cancer cell proliferation and promotes apoptosis and that its low expression is associated with poor prognosis in HCC patients (23). MMP-21 promotes macrophage recruitment by increasing CCL-14 levels and M2 macrophage polarization by increasing CSF-1 and FGF-1 expressions, thereby regulating the immune microenvironment and metastasis of HCC (24). The CCL20-CCR6 axis has been reported to be associated with a variety of cancers, including HCC, colorectal cancer, breast cancer, pancreatic cancer, cervical cancer and renal cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the exosomes can further reduce the efficacy of chemotherapy for HCC ( Giallombardo et al, 2016 ). Evidences show that exosome-mediated cellular communication is involved in drug resistance ( Li Y et al, 2021 ; Lu et al, 2021 ; Zhou J et al, 2022 ). It was reported that circZFR was highly expressed in CAFs and cisplatin-resistant HCC cells ( Zhou Y et al, 2022 ).…”
Section: Exosomes In Cancer Therapymentioning
confidence: 99%
“…In the TEM, the M2 TAMs are the major cell types of macrophages and associate with a poor clinical outcome in HCC. It is well known that M2 TAMs usually promote tumor growth, malignance, and metastasis ( Deng et al, 2021 ; Zhou J et al, 2022 ). In the TME of HCC, tumor-derived exosomes can promote the M2 polarization of macrophages ( Kwon et al, 2020 ).…”
Section: Exosomes In the Tmementioning
confidence: 99%